L’album de jeunesse narratif comme support pour déclencher le processus interprétatif en lecture littéraire chez les apprenants de deuxième année moyenne - Benchennouf , Houda; Ouhaibia , Billel (Milev Journal of Research and Studies, 2022)
If teaching/learning to read is a challenge for learners, parents and teachers; that of literary reading covers an additional difficulty for the various actors in the didactic process, as well in school and out-of-school contexts. This difficulty is-in part- doomed to the difference between literary and non-literary texts. Since learners are more used to the latter type of texts. On the other hand, literary texts conceal a lot of implicit which calls for a reflective interpretative work. Within the framework of our article we try to propose a didactic tool able to assist learners for the access to the comprehension as well as to the interpretation of this type of texts.